ANALYSIS OF TRADITIONAL METHODS FOR PREDICTING SOIL PRODUCTIVITY - Khidirova Charos Murodilloevna; Davronova Zarnigor Rizamat qizi (American Journals Publishing, 2025)
The article also discusses modern methods of crop yield assessment and forecasting, including the use of regression analysis based on satellite data. Particular attention is paid to short-term and medium-term forecasts that meet the requirements of simplicity, cost-effectiveness and automation. The proposed approaches allow one to take into account the depth of the forecast, which determines the choice of intuitive or formalized methods. The work contributes to the development of tools for sustainable agriculture and the maintenance of soil ecosystem services.
Keywords: Soil, plant, fertility, productivity, forecasting methods.